Estudos moleculares de enzimas do tipo tripsina presentes no intestino médio de larvas de Aedes aegypti - Soares, Tatiane Sanches [UNIFESP] (2009)
Aedes aegypti is the most important vector of human arboviral diseases and it is responsible for dengue and urban yellow fever transmissions. Trypsin-like enzymes plays an important role in the Ae. aegypti adult and larval life stages digestion. In the present work, we identified the two major trypsin-like enzymes of Ae. aegypti larval midgut through the trypsin cDNA fragments library construction. They are AAEL005607 and AAEL006371, with expression frequencies of 29.3% and 20%, respectively. Semi quantitative PCR analysis showed that the AAEL005607 was transcripted in all larval instars, but AAEL006371 appeared only in 3rd and 4th larval instars. In order to confirm the transcription data, trypsin-like enzymes from 4th instar larvae of Ae. aegypti midgut were purified by affinity, ionic exchange and reversedphase chromatographies. Purified trypsin presented molecular mass of 28 kDa by SDS-PAGE. Its partial amino acid sequence allowed us to suggest that the trypsin activity is encoding by AAEL005607 sequence. The purified trypsin (AAEL005607) showed Km value of 36.4 μM for Tosyl-Gly-Pro-Arg-pNa substrate and was strongly inhibited by AaTI and HiTI, both trypsin inhibitors, with Ki of 0.94 pM and 160 pM, respectively. In conclusion, for the first time, the major digestive enzyme of 4th larval instar of Ae. aegypti was identified and characterized.